STRATEGIC SYNERGY BETWEEN HUMAN RESOURCE MANAGEMENT AND MARKETING MANAGEMENT TO ENHANCE COMPETITIVE ADVANTAGE - Andre Wijaya Bermana; Muhammad Arif Ritonga; Dewi Ratna Bulan Siregar; Sontina Griche Tambunan (LPPM YPITI, 2026)
This study aims to analyze the strategic synergy between Human Resource Management and Marketing Management in improving competitive advantage within organizations. In the increasingly competitive business environment, companies are required to integrate internal resource management with effective marketing strategies to achieve sustainable organizational performance. This research uses a quantitative approach with data collection techniques through questionnaires distributed to employees and management involved in human resource and marketing activities. The data were analyzed using multiple linear regression analysis to determine the influence of Human Resource Management and Marketing Management on competitive advantage. The results of the study indicate that Human Resource Management has a positive and significant effect on competitive advantage through employee competency development, work motivation, and organizational commitment. In addition, Marketing Management also significantly influences competitive advantage through customer-oriented strategies, innovation, and market expansion. Simultaneously, the synergy between Human Resource Management and Marketing Management contributes significantly to strengthening organizational competitiveness. This study concludes that strategic collaboration between human resource management and marketing management can create sustainable competitive advantages and improve organizational performance in facing business competition.